Huso huso - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza (Zenodo, 2024)
9. Huso huso (Linnaeus, 1758) Common name. Beluga Taxonomy. Original description: Acipenser huso Linnaeus, 1758: 238 [Danube and the rivers of Russia; no types known]. Revisions. Berg (1948: 61). Illustrations. Berg (1948: 61, fig. 54); Kottelat & Freyhof (2007: 58-59, figs.). Distribution in Iran. —Distribution in River Basin: Caspian Sea.—Distribution in Ecoregions: 434-Kura-South Caspian Drainages, 450-Turan Plain, 452-Caspian Marine. Status in Iran. [Native].—Fil mahi, Mahi-ye khaviar.—Listed in previous checklists from Iran by Esmaeili et al . (2017 a, 2018); Jouladeh-Roudbar et al. (2020); Eagderi et al. (2022).—Iran material: None. Conservation. —IUCN: CR. Lepisosteiformes Published as part of Sayyadzadeh, Golnaz & Esmaeili, Hamid Reza, 2024, Freshwater lamprey and fishes of Iran: Reappraisal and updated checklist with a note on Eagderi et al. (2022), pp. 1-99 in Zootaxa 5402 (1) on pages 10-11, DOI:10.11646/zootaxa.5402.1.1, http://zenodo.org/record/10524097